WETLANDS CONSERVATION:AN INTEGRATIVE APPROCH - Waleska V. Manyari; Osmar A. Carvalho (European Scientific Journal, ESJ, 2014)
The emergence of an epistemology of complexity is a contemporary phenomenon strongly based upon technology that has claimed new research needs and revitalize old studied themes. The study of wetlands can be considered in this interdisciplinary context. The ability to respond in an organized manner to disturbances caused by seasonal flooding, a characteristic of wetlands ecosystems, define them as complex systems. The spatio-temporal heterogeneity of floodplain river systems is responsible for a diverse array of dynamic aquatic habitats. Thus, natural disturbances, represented by flooding and responsible for intensifying ecosystem heterogeneity, are the main factor in maintaining the ecological integrity. This requires knowledge of long-term patterns of inundation to preserve geomorphic formations, in other words, habitat diversity. Nevertheless, the processes that control water, sediment and nutrients transfer through the floodplain are not well understood. The maintenance of riverfloodplain connectivity has been recognized as a central strategy in ecosystem management. In this sense, remote sensing technology for a broad-scale systematic focus is particularly relevant. Research studies in this area provide new approaches for models useful in management on a regional scale. This chapter aims therefore to illustrate this wide research field involving current concepts and methodologies in order to improve the comprehension of the wetlands ecosystems as well as establish conservation criteria.